Evaluasi Kepemimpinan Camat Dalam Pembinaan Pemerintahan Desa Di Kecamatan Seluma Selatan Kabupaten Seluma - Rahiman Dani; Santri Nuver; Dodo Sutardi; Henny Aprianty; Hernowo Noviyanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The purpose of this study was to find out the description of the Regent of Seluma Regency, South Seluma Regency, regarding the development of village governance. This study uses an approach where the data obtained is presented and described or described and used as input to the authorities. Data collection tools with data collection techniques: Observation, interviews, and documentation. Then we analyze Permendagri 2018 number 20 to encourage village financial management: 1. planning, 2. implementation, 3. management, 4. Reporting, 5. Accountability, CIPP Leadership Assessment, Theory (Stufflebeam), Indicators: 1. contextual evaluation, 2, input evaluation, 3. process evaluation, and 4. product evaluation. The Village Head, Village Treasurer, and Chair of the BPD of Tangga Batu Village, Padang Genting, Seluma Market, and Padang Merbau as well as Chair of the South Seluma Administrative Body. The survey results show that the development of village government in the South Seluma administrative area by the Seluma District Director was successful.Â